Livestock in economic development - Jahnke, Hans E. (International Livestock Centre for Africa, 1979)
A note on agricultural development and factors affecting the role of livestock production in economic development w. ref. to the experiences of Australia, the ranching areas of South America and Germany, and the implications for livestock development in Africa.